Recent trend of industrial emissions in developing countries. (15th March 2016) - Geng, Yong; Wei, Yi-Ming; Fischedick, Manfred; Chiu, Anthony; Chen, Bin; Yan, Jinyue
Abstract: Greenhouse gas (GHG) emissions from industrial sectors are increasing, particularly in the developing world where pursuing industrialization has been highly addressed. This calls for further studies to learn and share experiences for developing countries. In order to fill in such a research gap, this special issue focuses on examining the recent trend of industrial emissions in developing countries. Among the manuscripts submitted to the Special Issue, twelve papers have been accepted after review, covering assessment indicators, tools and methods, and policies. Key industrial sectors, including cement, lime, aluminum, coal, mining, glass, soda ash, etc, have been investigated. Valuable policy insights have been raised, including wide scale upgrading, replacement and deployment of best available technologies, integrated information platforms, cross-cutting technologies and measures, a shift to low carbon electricity, radical product innovations, carbon dioxide capture and storage (CCS), demand on new and replacement products, systematic approaches and collaboration among different industries. These useful suggestions could be shared or learned by industrial policy makers or managers in the developing world so that the overall GHG emissions from their industrial sectors can be mitigated by considering the local realities.